Pengaruh Profitabilitas, Growth Opportunity, Likuiditas, dan Struktur Modal Pada Nilai Perusahaan - Indasari, Ade Pratiwi; Yadnyana, I Ketut (E-Jurnal Akuntansi; Vol 22 No 1 (2018)DO - 10.24843/EJA.2018.v22.i01.p27, 2018)
Companies that have go public in general are trying to increase the prosperity of investors through the improvement of corporate value which is the perception of investors to the success rate of the company to provide prosperity for shareholders. One of the methods used to analyze company value is by using Price to Book Value (PBV). This study aims to analyze the effect of profitability, growth opportunity, liquidity, and capital structure at the value of the company. The research population is all banking companies listed in Indonesia Stock Exchange period of 2012-2016 amounting to 43 bank companies and sample in research is 17 companies. This research type is descriptive research of quantitative. Financial statement data obtained by accessing the official website of Indonesia Stock Exchange. The results show that profitability, growth opportunity, and capital structure have a positive effect on firm value, while liquidity has no effect on firm value. Keywords: Profitability, growth opportunity, liquidity, capital structure, firm value